Iron-based catalysts under solar and visible radiation for contaminants of emerging concern removal - Domingues, Eva (2020)
The ubiquitous presence of CBZ, SMX and LRZ in water is a subject of increasing concern. This study represents a new approach in terms of these contaminants’ removal through Fenton process in three different ways, employing a solid catalyst, RM, which, alone, is a source of Fe3+ just as much is a source of environmental problems. Alongside RM, 100 mg/L of H2O2 were utilized as the initial solution’s pH remained unaltered. It was observed that, at these operating conditions, an appreciable degradation rate of contaminants was achieved. Solar photo-Fenton under visible light radiation led the way by attaining more than 50% removal for all three contaminants, reaching its peak when degrading around 62% of LRZ initially present. Therefore, RM, a residue from the alumina industry, seems to be a promising choice in terms of CECs degradation through Fenton process. Nevertheless, some parameters still need optimization, in order to achieve a better understanding and certainty of this oxidation process’ skilfulness for detoxifying CECs from the world’s water resources.